The career and the provisionality appointments in the Colombia labor public structure: A reflection about their functionality (2015)
As is stipulated in the 125 Article of the National Constitution of Colombia, the employments in the state organs and institutions’ belong to the administrative career, but there are some exceptions that the mentioned article describes. The general administrative career system is managed and Controlled by the Comisión Nacional del Servicio Civil which is the responsible for developing the merits contests as the ordinary mechanism to initiate the administrative career. Taking into account the ways to provide public employments it is necessary to do a reflection about the linking through the provisional appointments and also to do an analysis of these appointments with relation to the administrative career rights.